Entanglement and quantum phase transition in the anisotropic two-dimensional XXZ model. (March 2020) - Lima, L.S.
Abstract: The thermal entanglement in the spin-1 two-dimensional Heisenberg antiferromagnetic chain, with ion-single anisotropy, square lattice and in the neighborhood of critical anisotropy D c is studied employing Schwinger bosons. In particular, we discuss the effect of the variation of the critical anisotropy D c that separates the topological order of vortices for D < D c from the disordered phase for D > D c, on thermal entanglement. Furthermore, we analyze the effect of quantum phase transition described in the diagram D c vs. J 2 (second neighbors interactions ) on entanglement for a particular class of two-dimensional Heisenberg models which presents different exchange interactions J x and J y on x and y directions on square lattice. Highlights: The von Neumann entropy is calculated. The Gibbs state is considered. The effect of quantum phase transitions on entanglement is investigated.